Development of a flavor fingerprint by HS-GC–IMS with PCA for volatile compounds of Tricholoma matsutake Singer. (30th August 2019) - Li, Mengqi; Yang, Ruiwen; Zhang, Hao; Wang, Silu; Chen, Dong; Lin, Songyi
Highlights: Fingerprint of T. matsutake was established by HS-GC–IMS combined with PCA. Differences of flavor compounds in stipe and pileus of T. matsutake were analyzed. Effects of hot air drying on volatile compounds of were analyzed. Abstract: The flavor fingerprint of Tricholoma matsutake Singer was developed and volatile compounds were investigated by HS-GC–IMS fingerprinting combining with PCA. A total of 25 typical target compounds were identified. The differences of flavor compounds in pileus and stipe of Tricholoma matsutake Singer from different areas were observed. After drying, the concentration of C8 compounds, including 3-octanone, 3-octanol, 1-octen-3-one and 1-octanol, decreased, while the concentration of methanol and 1-pentanol increased. Subsequently, PCA was performed based on the signal intensity of the identified violate compounds, and the results clearly showed that the samples in a relatively independent space would be well distinguished. Combining the signal intensity of the identified violate compounds by HS-GC–IMS and PCA, the samples from different portions of Tricholoma matsutake Singer and different areas were distinguished. The results showed that the flavor fingerprint of Tricholoma matsutake Singer were established by HS-GC–IMS and PCA based on the identified volatile compounds.